The assessment technology of energy critical infrastructure. (15th January 2016) - Augutis, Juozas; Jokšas, Benas; Krikštolaitis, Ričardas; Urbonas, Rolandas
Highlights: We developed criticality assessment method for the critical energy infrastructures. This methodology is applicable for the mixed energy systems assessment. The systems component criticality assessment is performed. Abstract: In order to keep state's economical development and national security, it is necessary to secure integrity and functionality of energy infrastructure. Developed new criticality assessment method for the critical energy infrastructures is applicable to the assessment of mixed energy system infrastructures, taking into account functional relations between infrastructures and their elements. Component criticality assessment of critical energy infrastructures is performed taking into account the entire energy sector operation. Such assessment enables better quantitatively defining criticality of these components in terms of final energy consumers. The optimization methods were used to simulate a real system (to implement allocation of demands of district heating and electricity for generation technologies).